ONLINE LEARNING CHALLENGES: NEED FOR EVOLVING MODELS - Bentz, David T.; Lazarevic, Bojan (European Scientific Journal, ESJ, 2015)
This paper proposes that online learning theory can be enhanced by looking at research outside of education.Models such as the Community of Inquiry and the Transactional Distance Theoretical Model provide a utility toward structuring, conceptualizing, understanding, and analyzing online education. The ongoing research based on these models continues to explore and recommend as practice that the instructor holds "the keys" as to how the online learning environment will be formulated, shaped, and conducted. The assertion from this perspective continues that instructors through proper or improper structuring, guidance, and/or facilitation and design of their online learning environments may or may not be successful in their teaching. Research outside of education explores implications for online education from a biological and human behavior perspective, which includes analysis of innate brain wiring and emergent research regarding student emotional responses. If we think in terms of the online learning context and the apparent innate desire by all while learning to "connect" to one another, mirroring neurons and the advancement of their understanding could and should be monitored closely as more information and evidence emerges that may have valuable revelations about improving learning and learning outcomes within asynchronous learning environments. "Setting up" the space for learning is not enough for an online educator to understand. Having insight into one's own and others' personal relational dynamics and group dynamics is critical in facilitating online learning environments. Understanding the psyche of individuals and having the ability to intuit human behavior is equally important.